Economical point in sequestering CO2 into coal bed - methane production on based Turkish coal mines - Tosun, Yıldırım İsmail (IEEE 2013, 2013)
Unmineable coal seams can be used to store CO2 because the CO2 molecules fill the pores and attach to the surface of coal. The technical feasibility, however, depends on the permeability of the coal bed. In the process of filling pores and absorption to the coal surface, the sequestering the CO2 in coal mines releases methane in Turkish coal mines. Burning the resultant methane, however, would negate some of the economic view of sequestering the CO2. Economic advantages of the sequestering the CO2 were defined for economical view by coal bed methane gas production and green energy production in Turkey. Also economic view of designed work was comprising sequestering the CO2 into the coal bed in order to improve coal bed methane production in Sirnak Asphaltite Coal Mines. CO2 capturing, transporting and sequestering costs with methane drainage decreased from original cost of 14 $/ton CO2 to near11$/ton of CO2.
Keywords: CCS, Cost of CO2, capturing and storing CO2, coal bed methane, sequestering the CO2